Lipoteichoic acid deficiency permits normal growth but impairs virulence of Streptococcus pneumoniae - Heß, Nathalie (Nat Commun, 2017)
Teichoic acid (TA), a crucial cell wall constituent of the pathobiont Streptococcus pneumoniae, is bound to peptidoglycan (wall teichoic acid, WTA) or to membrane glycolipids (lipoteichoic acid, LTA). Both TA polymers share a common precursor synthesis pathway, but differ in the final transfer of the TA chain to either peptidoglycan or a glycolipid. Here, we show that LTA exhibits a different linkage conformation compared to WTA, and identify TacL (previously known as RafX) as a putative lipoteichoic acid ligase required for LTA assembly. Pneumococcal mutants deficient in TacL lack LTA and show attenuated virulence in mouse models of acute pneumonia and systemic infections, although they grow normally in culture. Hence, LTA is important for S. pneumoniae to establish systemic infections, and TacL represents a potential target for antimicrobial drug development.